2016
DOI: 10.1155/2016/1917268
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Intraocular Lens Power Calculation Formulas for Highly Myopic Eyes

Abstract: Purpose. To evaluate and compare the accuracy of different intraocular lens (IOL) power calculation formulas for eyes with an axial length (AL) greater than 26.00 mm. Methods. This study reviewed 407 eyes of 219 patients with AL longer than 26.0 mm. The refractive prediction errors of IOL power calculation formulas (SRK/T, Haigis, Holladay, Hoffer Q, and Barrett Universal II) using User Group for Laser Interference Biometry (ULIB) constants were evaluated and compared. Results. One hundred seventy-one eyes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 25 publications
1
41
0
2
Order By: Relevance
“…As the latest formula, excellent agreement by the two biometers was demonstrated in Barrett Universal II formula in the present study, this might due to the excellent agreement found in the AL and ACD measurements as discussed above. The findings by the present study that Haigis and Barrett Universal II formulas provided the most reliable and accurate IOL power prediction was also supported by other studies [23][24][25][26] .…”
Section: Discussionsupporting
confidence: 91%
“…As the latest formula, excellent agreement by the two biometers was demonstrated in Barrett Universal II formula in the present study, this might due to the excellent agreement found in the AL and ACD measurements as discussed above. The findings by the present study that Haigis and Barrett Universal II formulas provided the most reliable and accurate IOL power prediction was also supported by other studies [23][24][25][26] .…”
Section: Discussionsupporting
confidence: 91%
“…According to the clinical survey of the Japanese Society of Cataract and Refractive Surgery in 2018, [1] the SRK/T formula is currently still the most used formula for intraocular lens (IOL) power calculation in Japan. [2] Recently, it has been demonstrated that the Barrett Universal II formula provided a higher predictability than the SRK/T formula, especially in eyes with long axial length [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the previous three generations of formulas, the fourth-generation formula takes the effective IOL position (ELP) into account, and to some extent realizes the individualization of the IOL calculation. Recently, the fifth-generation formula Barrett Universal II has been applied to the clinic 15 .…”
mentioning
confidence: 99%